2018
DOI: 10.1096/fj.201700573r
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Dnmt3a increases Gdf5 expression with suppressed satellite cell differentiation and impaired skeletal muscle regeneration

Abstract: DNA methylation is an epigenetic mechanism regulating gene expression. In this study, we observed that DNA methyltransferase 3a (Dnmt3a) expression is decreased after muscle atrophy. We made skeletal muscle-specific Dnmt3a-knockout (Dnmt3a-KO) mice. The regeneration capacity after muscle injury was markedly decreased in Dnmt3a-KO mice. Diminished mRNA and protein expression of Dnmt3a were observed in skeletal muscles as well as in satellite cells, which are important for muscle regeneration, in Dnmt3a-KO mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Especially as PPARs and their coactivators are associated with improvements in training programs for weight reduction (29), aerobic performance (49,52,60,61) and resistance training load capabilities (1). In this manner, the ketogenesis and other metabolic factors determined by PPARA indicate an individual response to strength and power training (1), and satellite cell proliferation determined by GDF5 can indicate a potential to regenerate from a long term physical load (18). Regarding the fact that the interaction of these genes in terms of performance, injury prevention and fatigue factors was not analysed, the authors suggest that this analysis should be performed in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially as PPARs and their coactivators are associated with improvements in training programs for weight reduction (29), aerobic performance (49,52,60,61) and resistance training load capabilities (1). In this manner, the ketogenesis and other metabolic factors determined by PPARA indicate an individual response to strength and power training (1), and satellite cell proliferation determined by GDF5 can indicate a potential to regenerate from a long term physical load (18). Regarding the fact that the interaction of these genes in terms of performance, injury prevention and fatigue factors was not analysed, the authors suggest that this analysis should be performed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor alpha (PPARA) and growth differentiation factor (GDF5) genes have been associated with power performance (48), stress fractures (66) and muscle regeneration (18). Specifically, it has been suggested that PPARA predicts anaerobic trainability (1), and aerobic trainability (43,47,49), while GDF5 regulates the response of the proliferation satellite cell (18) (crucial after resistance training), meniscus injury incidents, and knee joint function recovery (14).…”
Section: Physical Performance and The Risk Of Injury Have Been Associmentioning
confidence: 99%
“…Several previous studies have focused on DNMT3A gene knockout in human or mouse-resourced cells, including human embryotic stem cells, human leukemia cells K562, mouse hematopoietic stem cells, as well as mouse somatic cells [2,14,27,28]. Compared to mouse cells, human cells are less tolerant to DNMT3A de ciency and it can cause lethality and genomic instability in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have focused on DNMT3A gene knockout in human or mouse-resourced cells, including human embryotic stem cells, human leukemia cells K562, mouse hematopoietic stem cells, as well as mouse somatic cells (Banaszak et al, 2018;Hatazawa et al, 2018;Jeong et al, 2018;Liao et al, 2015). Compared to mouse cells, human cells are less tolerant to DNMT3A deficiency and it can cause lethality and genomic instability in the cells.…”
Section: Discussionmentioning
confidence: 99%